Non-vibrate palm oil tree harvesting cutter using DC motor - Zamzuri, Hamedon; Ammar Zakwan, Abdullah; Ismayuzri, Ishak; Muhammad Hasnulhadi, Mohammad Jaafar (Springer Science and Business Media Deutschland GmbH, 2022)
Long exposure use of palm oil tree harvesting cutter powered by fuel engine can give risk of Hand Arm Vibration Syndrome (HAVS) disease, due to the transmitted vibration produced from the motorized cutter. In this paper, a new design of harvesting cutter which was powered by DC motor was proposed. Results shows that the vibration value were significantly low compare to the conventional motorized cutter; ranging between 0.04 and 0.29 m/s2.